Broussonetia kampferi Sleb. & Zucc, and Rhododendron obtusum (Lindl.) Planch. New to Indian Flora - Naithani, H. B. (Indian Forester, 1981)
Broussonetia kampferi Sieb. & Zucc. (Moraceae) and Rhododendron obtusum (Lindl.) Planch. (Ericaceae), native of China and Japan respectively have recently been collected from Subansiri district of Arunachal Pradesh and their occurrence is being reported for the first time from India.